Xenarthra (Mammalia) from a new late Neogene fossiliferous locality in Northwestern Argentina - Zurita, Alfredo Eduardo (2017)
Northwestern Argentina contains one of the most complete continental late Neogene (ca. 9e2.58 Ma) fossiliferous sequences in South America, especially in the current territories of the Catamarca, Tucumán and Jujuy provinces. More precisely in Jujuy Province several localities bearing mainly fossil mammals have been reported at the Quebrada de Humahuaca in the Uquía, Maimar a and Tilcara formations, in which the clade Xenarthra (Mammalia) is well-represented. In this scenario, the fossiliferous potential of other localities of Jujuy Province are less known, especially in those areas located at the northwest end of Argentina, bordering Bolivia in the Northern Puna. A new late Neogene fossiliferous locality near Calahoyo (3639 m.a.s.l), Jujuy Province, is here reported. The materials, belonging to Xenarthra, were exhumed from the base of the Tafna Formation which was deposited in a sedimentary basin by alluvial and/or fluvial currents, undergoing transitions of various lacustrine episodes. The taxa include the Tardigrada Pyramiodontherium bergi (Megatheriidae) and the Cingulata Eosclerocalyptus sp. (Glyptodontidae) and Macrochorobates chapalmalensis (Dasypodidae). From a biostratigraphic viewpoint, this assemblage suggests a Late Miocene-Pliocene age for the base of the Tafna Formation, and partially contradicts the supposed Plio-Pleistocene age of this unit. Finally, the new specimens here described indicate that Xenarthra were taxonomically and ecologically diverse during the late Neogene in the northwest end of Argentina, since they are represented by at least three main lineages (sloths, glyptodontids and armadillos).